Design of an experimental system for scanning EMG method to investigate alterations of motor units in neurological disorders [Nörolojik bozukluklardaki motor ünite deǧiş ikliklerinin araştirilmasina yönelik taramali EMG yöntemi i̇çin bir deneysel sistemin tasarimi] - (:unkn) unknown (My University, 2009)
The aim of this study is to build an experimental scanning EMG system in order to reveal the significant differences in either length of cross-section of motor units (MU) or maximum amplitude between the subjects with juvenile myoclonic epilepsy and the healthy volunteers. Data obtained from the biceps brachialis muscles of the subjects were used to construct 3-D electrophysiogical maps of the motor unit territories through a M-File subroutine created in MATLAB 7.2. These maps were used to compute the length of cross-section of MUs either JME subjects or those of normal control (NC) and spinal muscular atrophy (SMA) group and to compare the groups in order to investigate the presence of the statistically significant differences between these groups in terms of length of cross-section of MUs and their maximum amplitudes. ©2009 IEEE.